2018
DOI: 10.15407/ujpe63.6.531
|View full text |Cite
|
Sign up to set email alerts
|

External-Electric-Field-Enhanced Uniformity and Deposition Rate of a TiO2 Film Prepared by the Sparking Process

Abstract: We have used an external electric field to increase both the uniformity and deposition rate of TiO2 films. The experiment is carried out by sparking-off titanium wires with a high dc voltage of 1 kV (field int = 10 kV/cm) and a limited current of 3 mA. The external electric fields ( ext) of 3, 6, and 9 kV/cm were applied to the sparking system for 1-5 hours. The as-deposited film morphology was characterized by scanning electron microscopy. The results clearly show that the films are only deposited on the exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Traiwatcharanon et al [38] reported that the size of the synthesized particle was ∼23 nm for a sparking time of 45 min. In this work, the average size of nanoparticles increases significantly to ∼40 nm for a sparking time of 3 h. The effect can be explained by equation (2) [39].…”
Section: Electrochemical Measurementsmentioning
confidence: 58%
“…Traiwatcharanon et al [38] reported that the size of the synthesized particle was ∼23 nm for a sparking time of 45 min. In this work, the average size of nanoparticles increases significantly to ∼40 nm for a sparking time of 3 h. The effect can be explained by equation (2) [39].…”
Section: Electrochemical Measurementsmentioning
confidence: 58%
“…The authors declare no conflict of interest. Magnetic forces can induce crystallization and is a valuable strategy for chemical free reactions, together with electric field [41], pressure [42], ultrasound [43] and sonication treatment [44].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…That is challenging to control the direction of nanoparticles to improve deposition rate, uniformity, and morphology of prepared films. In previous paper, an external electric field was applied to confine nanoparticles on the substrate for increase deposition rate and uniformity of the films 15 . However, this technique is only suitable for conductive substrates (insulating substrates are not recommended).…”
Section: Introductionmentioning
confidence: 99%